A critical review on inhibition of dark biohydrogen fermentation. (November 2017) - Elbeshbishy, Elsayed; Dhar, Bipro Ranjan; Nakhla, George; Lee, Hyung-Sool
Abstract: Dark fermentation of organic wastes for hydrogen gas (H2 ) production is an attractive strategy of being renewable and carbon neutral. However, various toxic or inhibitory compounds can significantly limit sustainable operation and widespread adoption of this biotechnology. The metabolism of fermentative microbes in dark fermentation system can be inhibited by excess substrate, micronutrients, macronutrients, metal ions, high temperature, acidic pH, un-dissociated organic acids, competitive microbes, and substrate-derived toxic substances. This review paper introduces these potential inhibitory compounds, inhibition mechanisms, and provides engineering perspectives on the control of inhibition.